2015
DOI: 10.1038/ejcn.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y levels are associated with nutritional status and cardiovascular events in adults with chronic kidney disease

Abstract: Our results suggested a relationship between CSF NpY levels and nutritional indices in CKD patients. High serum NpY concentrations may be a risk factor associated with CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…Maintaining the protein content in muscles may improve these patients' clinical outcomes. Early research attributed wasting to malnutrition and insufficient protein intake, and researchers focused on appetite-regulating pathways, such as neuropeptide signalling (Lu et al, 2015;Morley and Farr, 2008). However, epidemiological studies have concluded that the excessive morbidity and mortality of CKD patients is rarely attributable to malnutrition (Fouque et al, 2008;Stenvinkel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the protein content in muscles may improve these patients' clinical outcomes. Early research attributed wasting to malnutrition and insufficient protein intake, and researchers focused on appetite-regulating pathways, such as neuropeptide signalling (Lu et al, 2015;Morley and Farr, 2008). However, epidemiological studies have concluded that the excessive morbidity and mortality of CKD patients is rarely attributable to malnutrition (Fouque et al, 2008;Stenvinkel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Perceived stress has been presented as a persistent precipitating effect in increasing T H 2 responses in asthmatic patients, and this effect might be mediated by peripheral blood levels of neuropeptide Y. 124 Neuropeptide Y levels consistent with a dampened response associated with chronic psychological stress were lower among young patients with acutely exacerbated and nonexacerbated asthma compared with healthy control subjects. Among asthmatic patients, neuropeptide Y appeared to play a role in the association between perceived stress and the persistently increased IL-4 levels of the type 2 immune response.…”
Section: Advances In Cytokines and Cellsmentioning
confidence: 99%
“…The concentration of serum NPY increases, but cerebrospinal fluid (CSF) NPY decreases with the progression of CKD. A low concentration of CSF NPY was associated with cachexia, reduced energy intake, and muscle-wasting among CKD patients [ 70 ]. It has been observed that higher serum NPY levels prognosticate cardiovascular mortality among dialysis patients [ 71 , 72 ].…”
Section: Adipokines and Their Influence On Pathogenesis Nutritional D...mentioning
confidence: 99%